Analysis of the Financial Performance of the Regional Government of North Sumatra Province in the Post–COVID-19 Period - Alia Rohali; Irawan Irawan; Vina Arnita (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the financial performance of the Government of North Sumatra Province in the post-Covid-19 period from 2021 to 2024 based on the ratios of financial independence, effectiveness, and efficiency. This research employs a quantitative descriptive approach using secondary data derived from the Regional Budget Realization Reports published by the local government. The results indicate that the financial independence ratio ranges from 17% to 24%, categorized as very low with an instructive relationship pattern, reflecting a high dependence on central government transfers. The effectiveness ratio ranges from 90% to 96% and is classified as effective despite fluctuations, while the efficiency ratio ranges from 97% to 100% and is considered less efficient because regional expenditures nearly absorb all revenues. Overall, the post-pandemic financial performance demonstrates relatively effective revenue realization; however, significant challenges remain in strengthening fiscal independence and improving expenditure efficiency.